Upaya Peningkatan Minat Belajar Bahasa Arab Peserta Didik Melalui Penggunaan Media Wordwall Di Kelas Xii Madrasah Aliyah Swasta Nurul Azmi Medan - Sakinah, Nur; Harfiani, Rizka (EL-EMIR Institute, 2025)
This research is motivated by the low learning interest of students in the Arabic language subject at Grade XII of Madrasah Aliyah Swasta Nurul Azmi Medan. Based on the results of observations and interviews with several teachers and students, it was found that the learning methods used were still conventional and monotonous, causing students to be less enthusiastic and easily bored. The purpose of this study is to examine the improvement of students’ learning interest through the application of the Wordwall learning media. This media was chosen because it is visual, creative, and encourages active student engagement in creating learning materials. The study employed Classroom Action Research (CAR) using Kurt Lewin’s model, which consists of two cycles. Each cycle included the stages of planning, implementation, observation, and reflection. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The pre-cycle observation of 19 students indicated that learning interest was still relatively low, with an average achievement of 49% based on four interest indicators. This was evident from the improvement in students’ participation, attention, and enthusiasm during the learning process. The percentage of learning interest increased from 49% in the pre-cycle to 84% in Cycle I. Furthermore, it increased to 87% in Cycle II. These findings demonstrate that the use of Wordwall as a learning medium is able to create a more interactive and enjoyable learning atmosphere, while also providing opportunities for students to express their ideas creatively. Therefore, Wordwall can be considered an effective alternative learning medium to enhance students’ learning interest, particularly in theoretical subjects such as Arabic.